The Effects of Anthropogenic Land Use Changes on Climate in China Driven by Global Socioeconomic and Emission Scenarios - Dong, Na; Liu, Zhen; Luo, Ming; Fang, Chaoyang; Lin, Hui (Earth's future, 2019)
The land surface, which interacts with lower atmosphere, is subject to substantial amounts of human activities. It results in regional climate fluctuations and must be assessed with a combination of future socioeconomic and emission policies to improve regional resilience and responsive efficiency on global mitigation and adaptation. Spatial heterogeneity in regional climate induced by land use changes of future global socioeconomic and emission scenarios is explored. Comparisons are carried out among both historical and future land use‐induced regional meteorological changes to investigate various climatic roles of land use conversions in China. The underlying changes in the surface albedo, leaf area index, energy exchange, and water balances are also examined. It is found that the increase of the summer temperature and the diurnal temperature range are the largest under the fifth Shared Socioeconomic Pathway characterized by more intensive urbanization. While temperature increase from urbanization and deforestation can be offset by cooling from vegetation evaporation increase under the extreme Representative Concentration Pathway (RCP) 8.5, which has no climate mitigation policies and high greenhouse gas concentration. In addition, RCP4.5 scenario would cause an average temperature increase of 1.41°C by 2050 at an annual rate of 0.028°C in China. The global climatic forcing warms the entire region and enhances precipitation intensity, and these effects are more substantial than those by regional land use changes, showing a strong background influence. Our research reveals the future climatic responses to regional anthropogenic land use changes under various scenarios and policies and provides ways to downscale global mitigation impacts into regional insights. Key Points Land use change‐induced warming from urbanization would be offset by cooling from increased vegetation evaporation under RCP8.5 Total temperature changes under RCP4.5 scenario increase 1.41°C by 2050 at an annual ratio of 0.028°C due to land use changes Regional climatic intensity brought by the global climatic forcing is more than those by the regional land use change